A new mechanism for electron spin echo envelope modulation. - Morton, J; Tyryshkin, A; Ardavan, A; Porfyrakis, K; Lyon, SA; Briggs, G (2005)
Electron spin echo envelope modulation (ESEEM) has been observed for the first time from a coupled heterospin pair of electron and nucleus in liquid solution. Previously, modulation effects in spin-echo experiments have only been described in liquid solutions for a coupled pair of homonuclear spins in nuclear magnetic resonance or a pair of resonant electron spins in electron paramagnetic resonance. We observe low-frequency ESEEM (26 and 52 kHz) due to a new mechanism present for any electron spin with S > 12 that is hyperfine coupled to a nuclear spin. In our case these are electron spin (S = 32) and nuclear spin (I = 1) in the endohedral fullerene N@C(60). The modulation is shown to arise from second-order effects in the isotropic hyperfine coupling of an electron and (14)N nucleus.